Time and freestyle piling: a subjective approach to 3D printing. Issue 2 (3rd April 2019) - Cohen, Zach
ABSTRACT: This paper considers the influence of 3D printers on the temporality and subjectivity of making by looking at current 3D printing processes through the concept of 'duration' that was theorized by the philosopher Henri Bergson. The discussion is contextualized within technological developments at the turn of the twentieth century—specifically, European railways—that changed our perception of time. The foundational ideas of duration are introduced as a response to these developments. The contemporary technological concept of 'real-time computing' is presented to contrast with duration and set up an in-depth explanation of the delays inherent to the 3D printing process. These delays are discussed within the discourse of 3D printing and technological innovation, in general. Current maker-3D printer interactions are then critiqued. Finally, an alternative method of 3D printing concrete that is founded on working with its inherent delays is introduced, along with its implications for digital making and the act of making time.